The Challenges of Assessing Social Appropriation of Science and Technology (2019)
The interview with Tania Arboleda Castrillón who is professional in the field of social approval of science, technology and innovation. He answered questions about his study, and the development he has had in the country and its social influences, as well as the changes he has had with the advent of new technologies and the internet. It emphasizes that citizens must have the tools to develop a critical, thoughtful and analytical capacity.